Resilience of women and their households in times of crisis - Naterer, Andrej (Annales. Series historia et sociologia, 2023)
This article focuses on the survival strategies of women and is based on ethnographic research among women in Slovenia and Bosnia and Herzegovina between 2016 and 2020. Results show that (1) socio-cultural and historical context plays a crucial role in the level of perceptions of crisis, (2) the first and strongest response to crisis appears as mobilization of economic resources within their households, (3) women rely heavily on social capital and informal networks, (4) cultural factors appear as crucial for successful informal networking and (5) resilience evolves as an amalgam of different configurations of economic, social and cultural capital.
Keywords: formal practices; informal practices; odgovor na krizo; odpornost žensk; resilence; response to crisis; strategije preživetja; survival strategies; women; ženske študije